Complete genome sequences of the Serratia plymuthica strains 3Rp8 and 3Re4-18, two rhizosphere bacteria with antagonistic activity towards fungal phytopathogens and plant growth promoting abilities - Adam, Eveline (Stand Genomic Sci, 2016)
The Serratia plymuthica strains 3Rp8 and 3Re4-18 are motile, Gram-negative, non-sporulating bacteria. Strain 3Rp8 was isolated from the rhizosphere of Brassica napus L. and strain 3Re4-18 from the endorhiza of Solanum tuberosum L. Studies have shown in vitro activity against the soil-borne fungi Verticillium dahliae Kleb., Rhizoctonia solani Kühn, and Sclerotinia sclerotiorum. Here, we announce and describe the complete genome sequence of S. plymuthica 3Rp8 consisting of a single circular chromosome of 5.5 Mb that encodes 4954 protein-coding and 108 RNA-only encoding genes and of S. plymuthica 3Re4-18 consisting of a single circular chromosome of 5.4 Mb that encodes 4845 protein-coding and 109 RNA-only encoding genes. The whole genome sequences and annotations are available in NCBI under the locus numbers CP012096 and CP012097, respectively. The genome analyses revealed genes putatively responsible for the promising plant growth promoting and biocontrol properties including predicting factors such as secretion systems, iron scavenging siderophores, chitinases, secreted proteases, glucanases and non-ribosomal peptide synthetases, as well as unique genomic islands.